PLANTS USED AS CONSTRUCTION COMPONENTS OF VERNACULAR EARTHEN ARCHITECTURE IN LA RIOJA PROVINCE, ARGENTINA - Rolón, Guillermo; Picca, Pablo; Rosenfeldt, Sonia (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2012)
Building materials of plant origin are widely used in vernacular earthen architecture. Their signiicance is such that they can be found in a variety of applications, from auxiliary building components up to primary structural elements. The present paper identiies a variety of plant species, whose materials have been used in rural households in the province of La Rioja, Argentina. The study area is conined to the region of the province’s valleys, located within the botanical geographic region of Monte. The material collected from houses was later identiied in the laboratory, which was compared with known samples. Further information provided by the villagers was also taken into account. The aims of the study were to draw up a list of plant species used, and to establish which of their parts and what qualities are exploited for the purposes that they were employed. Plant material was identiied in: a) adobe and lattice iller material, b) ceilings, c) structures of lattice walls, d) woodwork, e) rooing systems and f) supporting structures in general. Plant materials tend to be present with more variety and quantity in the roofs. The use of plants responds to three types of speciic functions, as primary or secondary structural elements, surface inishing, and stabilizer. The results conirm that plant species have signiicant involvement in the shaping of earthen architecture in rural areas of this region in the province.